CONTRIBUTION OF ISLAMIC FINANCIAL INSTITUTION FINANCING TO INDONESIA’S EXPORT PERFORMANCE - Muhammad Bahrul Ulum; Ayu Geby Gisela Syaputri (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to examine the contribution of Islamic financial institution financing to Indonesia’s export performance using monthly time-series data from January 2022 to December 2024. Employing multiple linear regression analysis, the financing provided by Islamic Rural Banks, Islamic Commercial Banks, and Islamic Financing Institutions was analyzed to determine its effect on export value as the dependent variable. The findings indicate that the model explains 42.25% of the variation in Indonesia’s export performance. Partially, the results show that financing from Islamic Commercial Banks has a positive and significant influence on export value, whereas financing from Islamic Rural Banks and Islamic Financing Institutions does not exhibit a significant effect. The simultaneous test confirms that, collectively, financing provided by Islamic financial institutions contributes significantly to Indonesia’s export performance.